1997
DOI: 10.1111/j.1432-2277.1997.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

A rat model of monitoring liver allograft rejection

Abstract: Rat models are often used to study liver allograft rejection. We have established a model for rat liver allograft rejection, monitored by fine needle aspiration biopsy (FNAB), in the strain combination PVG-to-BN with a mean survival time of 37 k 20 days. In this model, we observed acute rejection with an intense peak of lymphoid blasts and lymphocyte-dominated inflammation in the FNAB [9.1 f 3.0 corrected increment units (CIU)], and an eventual increase in macrophages (up to 4.2 f 4.4 CIU), together with fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…We previously developed a rat model of acute liver allograft rejection that showed an intense inflammatory infiltrate in the portal areas 1 week postoperatively and developed relatively slowly into macrophage reaction, graft necrosis, and fibrosis within 36 Ϯ 20 days. 15 In this study, special attention was paid to the effect of CMV infection on the inflammatory response of rejection and histological alterations of the bile ducts and vascular structures of the liver graft. …”
mentioning
confidence: 99%
“…We previously developed a rat model of acute liver allograft rejection that showed an intense inflammatory infiltrate in the portal areas 1 week postoperatively and developed relatively slowly into macrophage reaction, graft necrosis, and fibrosis within 36 Ϯ 20 days. 15 In this study, special attention was paid to the effect of CMV infection on the inflammatory response of rejection and histological alterations of the bile ducts and vascular structures of the liver graft. …”
mentioning
confidence: 99%
“…No immunosuppressive drugs were given to any of the animals. We have previously demonstrated that, in this strain combination, liver allotransplantation results in prolonged acute rejection with an intense peak of lymphoid activation at 1 week after transplantation, leading to later macrophage-dominated response and advanced tissue damage at a mean survival time of 37 days [12]. Grafts were harvested at 1 week (n = 5 in the CMV group, n = 3 in the uninfected group) and at 4 weeks (n = 6 per group) so that we could observe both the peak of rejection and the more prolonged phase.…”
Section: Transplantation and The Rejection Modelmentioning
confidence: 92%
“…In this rat model of liver transplantation, there are intense signs of acute rejection at 1 week, with portal inflammation and endotheliitis in the graft. In the later phase, at 4 weeks, there is still portal inflammation, but clearly less than at the peak, and the histological pattern is that of necrosis, fibrosis, and bile duct proliferation in response to injury [12], CMV infection significantly increased portal inflammation and bile duct damage in the late phase [13].…”
Section: Statisticsmentioning
confidence: 98%
“…12 BN to BN syngeneic transplantations were performed for syngeneic controls. The rats were fed with regular rat food and tap water ad libitum.…”
Section: Ratsmentioning
confidence: 99%
“…11 We have previously characterized the rejection response in a rat liver transplantation model with a donor-recipient strain combination of PVG(RT1 c ) into BN(RT1 n ). 12 We wanted to study whether VAP-1 expression would be induced in acute liver allograft rejection. We have also previously shown that rat CMV (RCMV) increases inflammation, bile duct destruction ,and sinusoidal VCAM-1 expression in rat liver allografts with concomitant rejection.…”
mentioning
confidence: 99%